Protocol for 18F-FDG quantification in PET-CT whole-body exams - Velasques de oliveira, S. M.; Carlos, M. T.; Carneiro, M. P.; Da silva, J. W. E.; Kasai, E. P.; Oliveira, A. R. N.; Boasquevisque, E. M. (Cellular and Molecular Biology, 2010)
The aim of the present work is to propose a protocol for quantification of 18F-FDG activities at organ level through whole body exams with Positron Emission Tomography. They were selected patients with normal uptake or a single tumor. In the period 2004-2005, 745 patients were studied. Among then, it was selected 97 adults for the normal uptake control group. The main studies were: intestine; colon, rectum, lung, lymphoma and melanoma, liver, esophagus, gonads and breasts. For "prospective screening”, it were selected 20 patients with the identical physical characteristics of the control group. For internal dosimetry, the main organs should be elected according the kinetics of 18F-FDG, either considering normal uptake or pathologies. Absorbed doses due to Computed Tomography and F-FDG uptake were estimated. Comparisons between internal and external exposures, for the same organ, point out higher doses due to external irradiation, except for bladder and kidneys. For individual dose estimation, parameters such the effective half-life should be known and this information may be achieved by an adaptation of the routine protocol.